2011
DOI: 10.1101/gad.1991811
|View full text |Cite
|
Sign up to set email alerts
|

Initial transcribed region sequences influence the composition and functional properties of the bacterial elongation complex

Abstract: The bacterial RNA polymerase (RNAP) holoenzyme consists of a catalytic core enzyme (a 2 bb'v) in complex with a s factor that is essential for promoter recognition and transcription initiation. During early elongation, the stability of interactions between s and the remainder of the transcription complex decreases. Nevertheless, there is no mechanistic requirement for release of s upon the transition to elongation. Furthermore, s can remain associated with RNAP during transcription elongation and influence reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 44 publications
(71 reference statements)
2
64
0
Order By: Relevance
“…Although the resolution of our ChAP-chip analysis did not permit discrimination of RNAP accumulation at promoters or promoter-proximal regions, we favor the possibility of accumulation at promoter-proximal pausing, since B. subtilis RNAP is known to form unstable open complexes and synthesize smaller amounts of abortive transcripts than E. coli RNAP (2,40). Recently, it was reported that the pausing of RNAP in E. coli is induced by direct and sequence specific interactions of RNAP with promoter-like sequences (6,29). However, we have not yet found any correlation between RNAP stalling and promoter-like sequences at the promoter-proximal regions in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the resolution of our ChAP-chip analysis did not permit discrimination of RNAP accumulation at promoters or promoter-proximal regions, we favor the possibility of accumulation at promoter-proximal pausing, since B. subtilis RNAP is known to form unstable open complexes and synthesize smaller amounts of abortive transcripts than E. coli RNAP (2,40). Recently, it was reported that the pausing of RNAP in E. coli is induced by direct and sequence specific interactions of RNAP with promoter-like sequences (6,29). However, we have not yet found any correlation between RNAP stalling and promoter-like sequences at the promoter-proximal regions in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…A fraction of RNAP is anchored to the promoter after initiation of RNA synthesis via persistent binding of 70 to the core promoter sequence in some E. coli promoters, and Gre factors upregulate transcription initiation from these promoters. In addition, E. coli RNAP often binds and stalls at Ϫ10-like sequences located downstream of the core sequence after promoter escape (6,11,21). The data obtained from in vivo KMnO 4 mapping suggest that E. coli RNAP stalls at the promoter-proximal regions in 10 to 20% of promoters, and GreA reduces the duration time of stalling at these regions for several genes (11).…”
mentioning
confidence: 99%
“…Some σ subunits release from core RNAP immediately upon the initiation of RNA synthesis (3). In contrast, the primary σ factor in Escherichia coli, σ 70 , may be associated in vivo with a fraction of transcription elongation complexes (TECs) even far downstream of the promoter (4)(5)(6)(7)(8). It is unclear whether this downstream association in vivo reflects retention of the initiating σ 70 subunit or binding of σ 70 after TEC formation and whether the σ 70 -TEC association is kinetically stable during transcript elongation (9).…”
mentioning
confidence: 99%
“…48 By showing that transcription-dependent loss of σ can be negatively modulated, previous studies have suggested the possibility that regulating the extent and time of σ release during elongation can influence not only elongation, but also RNA polymerase recycling and thus reinitiation. 49,50 Other in vitro studies have also shown that proteins as diverse as RapA, a bacterial homolog of eukaryotic SWI/ SNF proteins, and the ribosomal protein S1 can enhance transcription reinitiation, probably by counteracting inhibitory RNA polymerase-nucleic acid interactions, thus favoring polymerase recycling. 48,51 By contrast, transcription reinitiation could be thoroughly addressed in Archaea thanks to the availability of an in vitro system, reconstituted from purified Pyrococcus furiosus RNA polymerase and recombinant TBP and TFB, able to support multiple rounds of specifically initiated and terminated transcription.…”
Section: -27mentioning
confidence: 99%